Pengembangan Media Booklet Pendidikan Karakter dalam Pembelajaran Sejarah Berbasiskan Tari Tradisional di SMA Nizamia Andalusia Jakarta Timur - Herdin Muhtarom; Kurniawati Kurniawati; Abrar Abrar (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
The youth of Indonesia in the era of disruption face the problem of lacking understanding of local cultural philosophical values, which leads to the loss of moral values. To preserve local culture, it is essential to develop national character by internalizing local cultural values in behaviors and social interactions. The aim of this research is to determine the effectiveness of utilizing character education booklet media for teaching history based on traditional dance at SMA Nizamia Andalusia. This study employs a research and development (R&D) model, specifically the 4D development model (define, design, develop, disseminate). The results indicate that the percentage of agreement from assessments by experts in media, language, and design reached 71.43%. This suggests that the booklet model is theoretically and practically suitable for use in learning. Furthermore, the effectiveness of the booklet model was analyzed through pretest and posttest evaluations. The analysis results show a significant increase in students' learning achievement, with an average pretest score of 78.76 and a posttest score of 99.56. The Wilcoxon test indicated significant results with a p-value of 0.000, suggesting that the use of the booklet positively contributes to the improvement of students' academic performance.